OPTIMALISASI PENGEMBANGAN EKONOMI MARITIM DI PROVINSI SULAWESI TENGGARA - Syamsir Nur; Roslindah Daeng Siang (Program Studi Agrobisnis Perikanan, Fakultas Perikanan dan Ilmu Kelautan, UHO, 2016)
The economic opportunities of the utilization of marine resources is so large in Southeast Sulawesi has been duly made a great contribution also for the improvement of the regional economy, and even become the driving sectors of the regional economy are dominant. However, the potential of the maritime sector has not been optimally, which is characterized by the contribution of the fisheries sector to the regional economy that is still lower than the agricultural and plantation sectors and socio-economic conditions of the people who come into contact with maritime sector has not been encouraging. This study aims to identify policies that support the maritime economy and maritime economic development strategy in Sulawesi. The result showed that there are various policies identified in supporting the development of the maritime economy in Southeast Sulawesi, among others: the policy in the field of regional economic development, policies in the field of transport, policies in the field of fisheries policy in the field of development of tourism and creative economy, policy development in the field of infrastructure development cantonal. Various strategies that can be taken in the optimization of the development of the maritime economy in Southeast Sulawesi based on the potential and opportunities of making marine (maritime) as the leading sector in the economic development area.Keywords: Maritime Economy, Planning, Development